Design of a mobile augmented reality-based indoor navigation system - Ng, Xin Hui *; Lim, Woan Ning * (2020)
GPS-based navigation technology has been widely used in most of the commercial navigation applications nowadays. However, its usage in indoor navigation is not as effective as when it is used at outdoor environment. Much research and developments of indoor navigation technology involve additional hardware installation which usually incur high setup cost. In this paper, research and comparisons were done to determine the appropriate techniques of indoor positioning, pathfinding, and route guidance for an indoor navigation method. The aim of this project is to present a simple and cost effective indoor navigation system. The proposed system uses the existing built-in sensors embedded in most of the mobile devices to detect the user location, integrates with AR technology to provide user an immersive navigation experience. In this project, an indoor navigation mobile application was developed and tested. The development demonstrates the usage of Indoor Atlas which enables indoor positioning through technology fusion to detect user’s position and obtain the route to destination, and AR Core to display AR guidance using the computed route. Surveys were carried out to gauge the efficiency of the method and to gather the feedback from the participants. The architecture of the method and the demonstration of the application is presented.